2012
DOI: 10.1103/physreve.85.061125
|View full text |Cite
|
Sign up to set email alerts
|

Resonance dynamics evoked via noise recycling procedure

Abstract: We study the effect of noise recycling on nonequilibrium escape dynamics in a bistable system. For small noise, the non-Markovian problem is reduced to a two-state model with the master equation depending on not only the current state but also the earlier state, based on which we are able to derive the analytical formulas for the switching rate, the autocorrelation function, and the power spectrum density (PSD). Both the theoretical and the numerical results show that, with modulating the time delay in noise r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 31 publications
1
13
1
Order By: Relevance
“…Similar recycling delay evoked stochastic resonance dynamics are also reported in Sun's work [14], in which the best resonant signal may be obtained at moderate recycling delay level, but further control of the original noise effect are not found in that work. In many other investigations, recycling delay is also reported to be able to adjust the noise effects [5,[7][8][9]13].…”
Section: B Recycling Evoked Resonance Dynamics: the Basic Reason Forsupporting
confidence: 67%
See 2 more Smart Citations
“…Similar recycling delay evoked stochastic resonance dynamics are also reported in Sun's work [14], in which the best resonant signal may be obtained at moderate recycling delay level, but further control of the original noise effect are not found in that work. In many other investigations, recycling delay is also reported to be able to adjust the noise effects [5,[7][8][9]13].…”
Section: B Recycling Evoked Resonance Dynamics: the Basic Reason Forsupporting
confidence: 67%
“…This special kind of noise is also proved to significantly influence the traditional noise effects. It is found to be able to induce stochastic synchronization in a bistable system [5], control the noise enhanced stability in a metastable system [13] and evoke the resonance dynamics [14]. In both the conceptual Brusselator system [7] and the Van der Pol system [9], the recycling time controlled coherence resonance (CR) were reported.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…system have been investigated very recently. 37 The results have demonstrated that resonance behaviors, say coherence and stochastic resonance, can be evoked merely via the noise reinjection procedure. Nevertheless, it is worth mentioning that the particle in the reported researches was specified to trap in a potential without time delay, and the aimed model contained no time delay neither.…”
Section: Introductionmentioning
confidence: 96%
“…Since its innovative introduction by Benzi and his coworkers [6], SR has been studied extensively both theoretically and experimentally in stochastic bistable systems [7][8][9][10][11][12][13][14][15][16]. Meanwhile, several techniques have been developed or proposed to quantify SR phenomenon, such as signalto-noise ratio (SNR) [9], linear-response theory [10], residence-time distributions [11] and spectral power amplification [12].…”
Section: Introductionmentioning
confidence: 98%